PERAN CITRA HOTEL DAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL MELATI DI KAWASAN WISATA KUTA - Uttami, Ni Ketut Rahayu Laksmi; Rahyuda, I Ketut; Wardana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.09.TAHUN 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The rapid development of hotel industry in Bali is very competitive, particularly on the growth of budget hotels in Kuta Tourism Area which has increased in significant amount. The key to maintain competitive advantage in the competitive environment lies in how to deliver service quality in order to achieve customer loyalty . The effect of service quality to customer loyalty increases with the role of image and customer satisfaction. This study was conducted in budget hotels in Kuta Tourism Area through 200 respondents. The results of this study showed that service quality, hotel image, and customer satisfaction have a positive and significant effect toward customer loyalty. Hotel image and customer satisfaction are as well stated as a mediator in the service quality and customer loyalty relationship. Keywords: Image, Customer Satisfaction, Service Quality, Customer Loyalty /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}